2021
DOI: 10.1186/s13018-021-02519-x
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the inferior pole of the patella: tension band wiring versus transosseous reattachment

Abstract: Background The optimal surgical technique for the fixation of inferior pole patellar fracture remains controversial. The aims of this study were (1) to compare clinical and radiological outcomes following fixation of inferior pole patellar fracture by using tension band wire (TBW) and transosseous reattachment (TOR) without excision of the bony fragment and (2) to determine the risk factors for postoperative radiological loss of reduction. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 22 publications
0
29
0
1
Order By: Relevance
“…The tension band technique is a traditional fixation method for the treatment of patellar fractures. A study by Chang et al showed that tension-band fixation of patellar inferior-pole fractures showed low nonunion rates and reduced loss rates ( Chang et al, 2021 ), but the sample size was small. Tension-band technology can be applied to the fixation with relatively complete cortical bone support and tensile force ( Jang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The tension band technique is a traditional fixation method for the treatment of patellar fractures. A study by Chang et al showed that tension-band fixation of patellar inferior-pole fractures showed low nonunion rates and reduced loss rates ( Chang et al, 2021 ), but the sample size was small. Tension-band technology can be applied to the fixation with relatively complete cortical bone support and tensile force ( Jang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Existen varias técnicas de fijación descritas en la literatura que buscan preservar el polo inferior de la patela. 9 13 18 19 20 En la literatura más reciente, 21 el uso de alambres verticales y la fijación con placas tipo canasta ( basket plate ) se muestran como los métodos de fijación más confiables.…”
Section: Discussionunclassified
“…There are several fixation techniques described in the literature that seek to preserve the inferior pole of the patella. 9 13 18 19 20 In the more recent literature, 21 the use of vertical wires and basket plate fixation have been shown to be the most reliable fixation methods.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, anatomical reduction with strong internal fixation and early rehabilitation are important for patellar inferior pole fractures. Surgical options for treating patellar inferior pole fractures include tension band wiring (TBW), wiring through cannulated screws, vertical or cerclage wiring, plate fixation, partial patellectomy, and suture anchor (SA) fixation [ 6 ]. Appropriate treatment options vary depending on the degree of comminution and the fracture pattern in patellar inferior pole fractures; previous studies on such fractures were mostly case series and lacked a comparative analysis between each surgical treatment method.…”
Section: Introductionmentioning
confidence: 99%
“…However, TBW is often insufficient to achieve rigid fixation due to comminuted and small fracture fragments in comminuted inferior pole fractures [ 8 ]. Despite favorable postoperative outcomes after TBW in comminuted patellar inferior pole fractures, pull-out of Kirschner wires (K-wires), reduction loss, and implant irritation have been reported as common postoperative complications [ 6 , 9 ]. Moreover, additional surgeries are frequently necessary for implant removal due to symptomatic implants in patellar fractures treated with TBW [ 6 ].…”
Section: Introductionmentioning
confidence: 99%